Development of a prototype rotating vacuum / Muhammad Nazrin Shah Noor Azlan Shah - Noor Azlan Shah, Muhammad Nazrin Shah (2023)
This project is about a vacuum sealer that can help small entrepreneurs their domestic food manufacturing process. This machine can help to reduce minor problems and sometimes significant problems that hold back some of entrepreneurs by reducing the production to completely seal the product to maintain the freshness of the product and increasing the productivity of the production of the product. This project includes the designs and analysis for how the machine is fabricated so that it can function well to solve the problems that the small entrepreneurs faced. For the expected result, it is expected to meet the manufacturing requirement and function is achieved through out manufacture process.